Principles for forming a system of professional competences in the training of specialists in the sphere of labor safety - Yevtushenko, N. S.; Tverdokhliebova, N. E. (My University, 2023)
Today, many leading companies and state-owned enterprises formulate their requirements for personnel in the language of competencies. According to the international standard ISO 45001:2018 Health and Safety Management System, it is established that the enterprise has: determine the required level of competence; assess the current competence of the staff; develop training plans to reduce differences between required and existing levels of competence. Competence is understood as the unity of knowledge, professional experience, personal abilities and behavioral skills of an individual, determined by the goal, given situation and position.
Keywords: охорона праці; аудіт охорони праці; умови праці; безпека праці